Given differential equation is
"y''+3y'+2y = \\delta_6(t)" with conditions is "y(0)=0, y'(0)=-1" .
Taking Laplace transform on both sides, we get
"L(y'')+ 3L(y')+2L(y )= L(\\delta_6(t)) \\\\\n\\implies s^2 Y + 1 + 3 sY + 2 Y = e^{-6s}" where "Y = L(y)" .
"\\implies (s^2+3s+2) Y = e^{-6s} -1 \\\\\n\\implies Y =\\frac{ e^{-6s} -1}{s^2+3s+2} \\\\\n\\implies y =L^{-1}(\\frac{ e^{-6s} -1}{s^2+3s+2})"
So, "y =\\left(\\left(\\left(- e^{12 - t} + e^{6}\\right) \\delta_6(t )- 1\\right) e^{t} + 1\\right) e^{- 2 t}"
Comments
Leave a comment